Methylene Blue Adsorption on a Low Cost Adsorbent-Carbonized Peanut Shell - Gulen, Jale; Zorbay, Fatih (WILEY, 2017)
Carbonized peanut shell (CPS), a low cost adsorbent was investigated for adsorption of methylene blue from its aqueous solution. Some experimental parameters like the effect of initial dye concentration, initial solution pH, phases contact time and temperature were investigated. Langmuir, Freundlich and Harkins-Jura isotherm models were applied to the experimental data and Langmuir model fitted best. Monolayer adsorption capacity was 5.34 mg/g according to the Langmuir model. Adsorption capacity/uptake of CPS was found comparable to the some other adsorbent materials. The kinetic and intra particle diffusion models were applied to the experimental data. The experimental reaction was progressed via pseudo second order kinetic model. The thermodynamic parameters were also evaluated.
Keywords: adsorption; methylene blue dye; peanut; isotherm; kinetic; thermodynamic; ACTIVATED CARBON; PHOTOCATALYTIC ACTIVITY; AQUEOUS-SOLUTION; TEXTILE EFFLUENT; INDUCED DEGRADATION; ZNO NANORODS; BASIC DYE; REMOVAL; SORPTION; NANOCOMPOSITE; Engineering; Environmental Sciences & Ecology; Marine & Freshwater Biology; Water Resources